Dial oceanographic and biogeochemistry variability in the northern Patagonian waters - Cornejo-D'Ottone, Marcela; Silva, Nelson; Contreras, Esteban (The Science of the total environment, 2025)
Fjords are subject to significant variability not only spatially, seasonally, and interannually but also on a daily scale due to the influence of tides and climatic events and terrestrial contributions that modify the water column and, therefore, the contribution of nutrients and waters of different temperatures and salinity. In the present study, we compare the daily variability of oceanographic and biogeochemical characteristics at two stations in northern Chilean Patagonia, one in the Reloncaví fjord, the northernmost Chilean fjord, with a strong terrestrial influence and anthropogenic activities, and the second in Ancud, east of the Chacao channel, with a direct influence of the Pacific Ocean. The sampling at each station was conducted in July 2013 (austral winter), a period typically characterized by high precipitation and river discharge, but low solar radiation and primary productivity. The study offers a snapshot of winter conditions with high-frequency sampling (1−3 h) for two days. The analysis shows two contrasting stations: i) a station with a high stratification and riverine influence in Reloncaví fjord driving the surface biogeochemistry, with stoichiometry indicators suggesting phosphorus deficiency and high silicic acid levels that could support diatom proliferation, while a deeper layer driven by tidal cycle with a lag of 6–10 h from the Puerto Montt station (69 km west) and ii) a quasi-homogeneous station at Ancud, with low influence of freshwater, lower silicic acid and higher N:P ratios, while the vertical oceanographic and nutrients distribution seems to be driven by tidal cycle with a lag of 2–3 h. Based on short-term oxygen level and nutrient ratios, both stations showed no immediate signs of eutrophication. However, this observation reflects only a snapshot, and seasonal variability or eutrophication cannot be ruled out without long-term monitoring. The oxygen and nutrient concentration differences between both stations reflect the biogeochemical processes during the water mass transportation. These results highlight the different drivers of the oceanographic and biogeochemical dynamic along the water column in the northern Patagonia ecosystems. However, as the study represents a short-term winter condition, it does not rule out the occurrence of seasonal or episodic oxygen depletion events. This emphasizes the importance of high-frequency studying and monitoring of the ecosystem. [Display omitted] •Daily variability of oceanographic and biogeochemistry conditions•Riverine contribution as a source of nutrients and stratification of the water column•Spatial differences of the tidal dynamic impacts•Changes in nutrient concentration and ratios as a source for surface primary production